ANALISIS KINERJA GURU BIMBINGAN DAN KONSELING DALAM PELAKSANAAN PROGRAM BIMBINGAN DAN KONSELING - andreas setiawan; Giyono Giyono; Ranni Rahmayanthi (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this research was to determine the performance of guidance and counseling teachers in the implementation of guidance and counseling program at SMPN in Kecamatan Tulang Bawang Tengah. Problems in this research is not optimal to implement guidance and counseling program at SMPN in Kecamatan Tulang Bawang Tengah year of 2012/2013. The problem is how the performance of guidance and conseling teachers in the implementation of guidance and counseling program at SMPN in Kecamatan Tulang Bawang Tengah year of 2012/2013. The method used in this research is descriptive method. The data collection technique using questionnaire and documentation. The population in this study was 11 guidance and counseling teachers at SMPN in Kecamatan Tulang Bawang Tengah year of 2012/2013. These results indicate that the performance of guidance and counseling teachers, in the implementation of guidance and counseling program considered good enough with result of percentage is 47%. Some aspects of guidance and counseling programs has been implemented well enough. However there are some aspects of guidance and counseling program showed unfavorable results. This is because there are teachers who are not from graduate study program of guidance and counseling, but still served as guidance and counseling teacher. Researchers recommend suggestions to: (1) guidance and counseling teachers are expected to improve performance in the implementation of guidance and counseling program. (2) the school is expected to better support guidance and counseling teacher in implement any activity guidance and counseling services. Keywords: Performance Analysis, Guidance and Counseling Program